Analyzing the Effects of a G137V Mutation in the FXN Gene - Faggianelli, Nathalie; Puglisi, Rita; Veneziano, Liana; Romano, Silvia; Frontali, Marina; Vannocci, Tommaso; Fortuni, Silvia; Testi, Roberto; Pastore, Annalisa (Frontiers in Molecular Neuroscience, 2015)
Reduced levels of frataxin, an essential mitochondrial protein involved in the regulation of iron-sulfur cluster biogenesis, are responsible for the recessive neurodegenerative Friedreich Ataxia (FRDA). Expansion of a GAA triplet in the first intron of the FRDA is essential for disease development which causes partial silencing of frataxin. In the vast majority of cases, patients are homozygotes for the expansion, but a small number of FRDA patients are heterozygotes for expansion and point mutations in the frataxin coding frame. In this study, we describe a newly-discovered point mutation (G137V). The patient P94-2, with a history of alcohol and drug abuse, showed a FRDA onset at the border between the classic and late onset phenotype. We applied a combination of biophysical and biochemical methods to characterize its effects on the structure, folding and activity of frataxin. Our study reveals no impairment of the structure or activity of the protein but a reduced folding stability. We suggest that the mutation causes misfolding of the native chain with consequent reduction of the protein concentration in the patient and discuss the possible mechanism of disease.